Mechanical performance of cup lump rubber modified asphalt mixtures incorporating polyphosphoric acid - Ansari, Anwaar Hazoor; Mohd Jakarni, Fauzan; Muniandy, Ratnasamy; Hassim, Salihudin; Elahi, Zafreen; Zair, Mohamed Meftah Ben (Elsevier, 2023)
Natural rubber (NR) producing countries face rubber production and price fluctuations. NR production’s high cost and low market price have produced an extensive demand for alternative applications of NR. This paper examined the influence of cup lump rubber (CLR) and polyphosphoric acid (PPA) on the mechanical performance of asphalt mixtures. The five modified blends were selected for the hot mix asphalt (HMA) performance analysis. The results revealed that the CLR increasing content in the bitumen ultimately increases the optimum bitumen content (OBC) for the asphalt mixture. There is a significant difference in the base mixture OBC (5.19 %) compared to the cup lump rubber-modified bitumens (CLRMBs). The CLRMB6 + 0.5PPA asphalt mixture OBC was 5.32 %, which is higher among all the mixtures. The rutting findings demonstrated that the control mixture exhibited the highest strain of 1.71 %, followed by CLRMB6 with 1.43 %, CLRMB3 + 0.5PPA with 1.1 %, CLRMB9 with 0.7 %, and CLRMB6 + 0.5PPA with the lowest strain of 0.47 %. The creep stiffness modulus of all mixtures met the minimum requirement of ≥75 MPa. The results implied that the CLR and the PPA displayed incredible potential to improve the asphalt mixture’s resilient modulus (MR). The CLRMB9 resilient modulus increased significantly by 22 % compared to the control mixture. The CLRMB6 + 0.5PPA has a higher MR of 5210 MPa than the other modified mixtures and the control mixture with 3521 Ma. Thus, the study’s findings suggest that the CLR, in conjunction with the 0.5PPA exhibits a decisive effect on the asphalt mixture performance and could be beneficial as a sustainable material in the pavement industry.